Non‐memory subjective cognitive concerns predict incident motoric cognitive risk syndrome. (19th May 2020) - Nester, C.; Ayers, E.; Rabin, L.; Verghese, J.
Abstract : Background and purpose: Motoric cognitive risk syndrome (MCR) is a predementia condition that combines slow gait and subjective cognitive concerns. As the earliest markers of MCR are relatively unknown, the role of subjective cognitive concerns was investigated to predict incident MCR in a well‐characterized prospective cohort of non‐demented older adults. Methods: Non‐demented MCR‐free older adults ( n = 476) from the Central Control of Mobility in Aging cohort completed gait, subjective cognition and neuropsychological assessment at baseline and follow‐up. Subjective concerns were analyzed via responses to 12 items from three validated measures, the Late‐Life Function and Disability Instrument – Disability Component, the Activities of Daily Living Prevention Instrument and the Geriatric Depression Scale, and were independent of items utilized to diagnose MCR. Cox proportional hazard models examined the association between cognitive concerns and incident MCR. Results: After 2.36 ± 1.4 years, 28 participants developed MCR. Executive functioning (adjusted hazard ratio 2.458, 95% confidence interval 1.094–5.524, P = 0.029) and mental clarity concerns (adjusted hazard ratio 3.917, 95% confidence interval 1.690–9.077, P = 0.001) were associated with incident MCR, controlling for age, sex, education and gait speed. Conclusions: Subjective cognitive concerns in non‐memory cognitive domains predict incident MCR. Although most MCR studies assess cognitive concerns about memory, our findings suggest the need to broaden the scope of subjective cognitive assessment to enhance the accuracy of diagnosis and prediction of future cognitive decline.